Therapeutic Targeting of the Staphylococcus aureus Accessory Gene Regulator (agr) System - Tan, Li; Li, Si Rui; Jiang, Bei; Hu, Xiao Mei; Li, Shu (Frontiers in Microbiology, 2018)
S. aureus can cause numerous different diseases, which has been attributed to its large repertoire of virulence factors, many of which are under the control of the accessory gene regulator (agr) quorum sensing system. Under conditions of high cell density, agr increases the production of many virulence factors, decreases expression of several colonization factors, and is intimately associated with the pathogenesis and biofilm formation of S. aureus. This review summarizes our current understanding of the molecular mechanisms underlying agr quorum sensing and the regulation of agr expression. The discussion also examines subgroups of agr and their association with different diseases, and concludes with an analysis of strategies for designing drugs and vaccines that target agr to combat Staphylococcus aureus infections